Wisata Ziarah Masjid Sayyid Arif Segopura sebagai Solusi Konseling Remaja Masjid Kota Pasuruan - Meilda Fitriana (Jurnal Al-Tatwir, 2022)
Pilgrimage can be a therapy, which consists of two words, namely therapy and pilgrimage. Therapy itself according to the Big Indonesian Dictionary (KBBI) is an attempt to restore the health of someone who is sick. Meanwhile, in Greek "Theraphy" means caring or nurturing and in Arabic it means healing or treatment. This study uses a qualitative method. This research was conducted in Pasuruans District. The research was conducted from June to August 2022. The research informants consisted of main informants and additional informants. The main informant is the youth counseling council at mosques in Pasuruan sub-district who live in Pasuruan sub-district. In the process of handling the counselee's problem, namely juvenile delinquency the counselor uses Pilgrimage Therapy which consists of several steps, namely the first stage (direction by researchers), the second stage (giving examples of the process pilgrimage therapy), the third stage (time, place, day and date of pilgrimage therapy by the counselee). The research informants are friends, teachers, parents or counselee's family, neighbors and the counselee himself. Data collection techniques include observation, interviews, and documentation. The results of the research from the implementation of pilgrimage therapy can be said to be successful, seen from the observations of researchers before and after the counseling process was carried out, the counselee has begun to show changes such as the counselee's emotions are more stable, calmer and the client's stress is reduced on negative things, so that it can become a better and more useful person.